Sequential Resource Allocation Schemes in Wireless Mesh Networks - 차재룡 (The Graduate School, Ajou University, 2013)
Wireless mesh networks (WMNs) are emerging communication networks consisting of nodes that automatically establish an ad-hoc network and maintain mesh connectivity. With the popularity of WMNs, supporting quality of service (QoS) over multihop radio links is becoming an important issue because end-to-end (ETE) delay increases quickly with the increase in the number of hops. Various QoS-aware scheduling schemes based on time division multiple access (TDMA) have been proposed for supporting a variety of applications such as voice and video calls in multihop WMNs. Basically, they have been focusing on determining minimum length schedules. Although such schemes reduce a frame length, they may bring about queuing delay which can increase ETE delay because they share a slot for multiple flows in a link. Meanwhile, the order of timeslots scheduled in a flow also may have an effect on ETE delay in multihop WMNs. Some papers have proposed scheduling schemes considering the order of timeslots. However, they all have assumed that there is always a centralized station in a network. Recently, many researches on network coding (NC) scheme have been introduced to increase the utilization of valuable resources in multihop WMNs. So far, almost all conventional works on NC have focused on the improvement of network throughput efficiency that is the original objective of NC. However, if an appropriate link schedule for NC is not considered, ETE delay may be increased even though NC gain can be obtained. Therefore, this dissertation first proposes a fully-distributed resource allocation scheme called sequential link schedule (SLS) that not only eliminates queueing delay but also considers the order of timeslots scheduled on a path. In the proposed SLS scheme, channel locking algorithm called time slot acquisition (TSA) is employed for interference free slot allocation in a distributed manner. Then, the multihop slot allocation (MSA) algorithm is carried out to sequentially allocate slots on the path. According to the analysis results, in case of deterministic packet arrival, the proposed SLS scheme shows shorter ETE delay, even though it starts the packet transmission with slightly greater frame length than that in case of the minimum length schedule (MLS). For the non-deterministic packet arrival having exponential distribution, the proposed SLS scheme shows a slightly lower delay performance. However, the proposed SLS scheme is more tolerable for a high packet interarrival rate than the MLS. In the next proposal, two bandwidth allocation schemes jointly combined with NC are proposed to reduce ETE delay and enhance resource utilization in the network. The first proposed section-based sequential scheduling scheme, which is flow-based one, employs a new concept, ‘section’, so that the slots scheduled on a path are sequentially arranged within a frame even when NC operation is performed. The second proposed scheme is a ‘duplicated allocation followed by resource release’ (DARR) based sequential scheduling scheme. The basic idea of the proposed DARR-based scheme is that, when the MSA algorithm has been initiated from the non-reference NC flow, an NC coordinator not only transfers an slot allocation (SA) packet to the next node of the non-reference NC flow but also again transfers another SA packet to the next node of reference NC flow before releasing the initially-allocated slots. By the simulation results, it is known that the proposed schemes show better delay performance than the conventional SLS-NC. Therefore, by applying the conventional XOR-based NC scheme to the link scheduling, the proposed schemes give more delay-efficient slot assignments that result in better channel utilization while at the same time using less network resources and energy. In conclusion, the proposed sequential scheduling schemes can give the sequentiality with NC gain guaranteed, thereby resulting in decreasing ETE delay and enhancing the resource utilization in multihop WMNs.
학위논문(박사)아주대학교 일반대학원 :전자공학과,2013. 2
Keywords: WMN; Sequential; Scheduling; QoS; Realtime; TDMA